(untitled) (ModaPalavra e-periódico, 2008)
Creativity is a phenomenon that arouses the interest and curiosity of people since the beginning of time. It is present in all that is human. The process of generating new ideas, products, art, science, among many other things, seems to be a talent that humanity has ever you need answers or innovative solutions to their problems and existential issues. This article discorre about the importance of being creative and the influence that the creativity question to personal life, school and by consequence, professional.